Amphipathic barbiturates as marine product mimics with cytolytic and immunogenic effects on head and neck squamous cell carcinoma cell lines - von Hofsten, Susannah; Langer, Manuel K.; Korelin, Katja; Magnussen, Synnøve; Ausbacher, Dominik; Anderssen, Trude; Salo, Tuula; Strøm, Morten B.; Bayer, Annette; Al-Samadi, Ahmed; Berge, Gerd (Frontiers in Pharmacology, 2023)
The incidence of head and neck squamous cell carcinoma (HNSCC) is increasing and the conventional treatments for this form of cancer can be tough. Despite the success of existing immunotherapies in some HNSCC patients, many do not respond to this type of treatment. Thus, the development of novel anti-cancer therapies should be prioritized. In the current study, the anticancer activity of a panel of novel compounds, herein termed marine product mimics (MPMs), against HNSCC cell lines is explored. The previously reported compound MPM-1, which is structurally related to the novel MPMs, was shown to have promising effects on the HNSCC cell line HSC-3. The results from the current study indicate that the novel MPMs are more potent than MPM-1 but cause a similar type of cell death. The results indicated that the MPMs must cross through the cell membrane to exert their action and that they are lysosomotropic. Further experiments showed that some of the MPMs could induce phosphorylation of eukaryotic initiation factor 2α (eIF2α) in HSC-3 and UT-SCC-24A cells, which indicates that they can activate the integrated stress response that is strongly associated with immunogenic cell death. Cell surface expression of calreticulin and release of HMGB1 and ATP, which are all hallmarks of immunogenic cell death, was also demonstrated in HSC-3 and UT-SCC-24A cells treated with MPMs. This suggests that the MPMs are interesting candidates for future HNSCC cancer therapies.